PROFIL KOMPETENSI LULUSAN PROGRAM STUDI PENDIDIKAN BAHASA ARAB PERSPEKTIF STAKEHOLDER - Maswani, Maswani (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2016)
This research was purposed to describe the pedagogical, professional, personal, and social competences of Junior High Madrasah Arabic language teachers, the graduates of Department of Arabic Education (DAE) FITK based on the perspective of the school principals, colleagues, and students in MGMP Madrasah Cooperation Group (KKM)of South Tangerang city. The quantitative approach was applied with descriptive qualitative method. The data of the research were obtained from interview, observation, and document research related to the analysis in comprehensive way. The populations were involving the junior high madrasah Arabic language teachers, the graduates of DAE FITK UIN Jakarta in MGMP KKM South Tangerang with the certified teachers as the samples. The result showed that the teachers have pedagogical, professional, personal, and social competences within good/high categorized besides having strengths and weaknesses in certain aspects.DOI: 10.15408/a.v3i2.4163